Systematic Safety Evaluation of Cold Plasma-Activated Liquid in Rabbits - Xu, Yujing; Peng, Sansan; Li, Bing; Wang, Shuai; Zhang, Hao; Li, Qiaosong; Liu, Zhijie; Guo, Bo; Liu, Dingxin; Xu, Dehui (Frontiers in Physics, 2021)
Plasma-activated liquid (PAL) can effectively and selectively kill various types of cancer cells both in superficial and deeper tumors. As a promising novel approach to oncotherapy, the safety of PAL is essential in the clinic but has not been thoroughly assessed. In myeloma and blood tumors, the pathogenesis is in the bone marrow cavity. We have therefore evaluated the safety of PAL in New Zealand rabbits by intra-bone marrow injection, and provide a basis of further clinical research and application of PALs. In this study, both a plasma jet and plasma surface were used to treat saline solution, phosphate-buffered solution, and cell culture medium, to produce PAL. Then, oscillograms and optical emission spectra were evaluated to characterize the plasma discharge. Acute toxicity tests and safety evaluation studies were conducted by intra-bone marrow injection of PAL into New Zealand rabbits, while control rabbits received saline only. Body weight, vital organ coefficient, organ appearance, organ histopathology, blood cell and hemoglobin parameters, and blood biochemical indicators were tested on the 30th day after injection. We found that there was no mortality or loss of mobility throughout the experimental period. Acute toxicity tests showed that there were no PAL-related side effects in rabbits receiving the maximum dose of 700 μL PAL. PAL treatments did not affect body weight, organ coefficient, organ appearance, organ histopathology, or blood biochemical indicators. However, the percentage of lymphocytes decreased while the percentage of neutrophil granulocytes increased compared with the control group. In summary, our results indicate that PAL can be safely injected into bone marrow of New Zealand rabbits without significant toxicity.